Teoretycznoprawne aspekty przedstawicielstwa organizacyjnego jako pragmatycznego sposobu reprezentacji osoby prawnej: [Legal aspects of oragizational representation as a pragmatic type of legal entity’s representation] (Studia Prawnicze / The Legal Studies, 2017)
The subject of legal entities’ representation in private law trading is of utmost importance because it affects the correctness of legal acts performed by these entities. The author, having analyzed the origins of legal entity’s representation and the form of legal entity’s representation on the grounds of European models (Germany) shows that in European countries of German legal traditions the model of organizational representation (organschaftlicher Vertretung) is being applied more and more commonly. On the grounds of Polish law the legal concept and model of the body of legal entities have based on the so called theory of bodies (organs) until recently. At present, under the influence of European solutions (Germany, Austria, Switzerland) there is a tendency to treat the bodies of legal entities as organizational representatives (of statute nature), i.e. the third – beside legal representation and based on contract - type of representation. It seems, however, that organizational representation constitutes a pragmatic alternative for the hitherto, formal concept of the theory of bodies (organs), which may substantially affect the flexibility of trading.